2009
DOI: 10.21608/ajesa.2009.4967
|View full text |Cite
|
Sign up to set email alerts
|

Typhlodromips swirskii (Acari: Phytoseiidae): A Predator of Eriophyid and Tetranychid Mango Mites in Egypt

Abstract: The predacious mite Typhlodromips swirskii (Athias-Henriot) successfully developed to the adult stage when fed on the motile stages of the mango bud mite Aceria mangiferae Sayed, the mango rust mite Metaculus mangiferae (Attiah), the leaf coating mite Cisaberoptus kenyae Keifer and nymphs of the mango red mite Oligonychus mangiferus (Rahman and Sabra)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The lower performance of Cydnoseius negevi towards Achroia grisella eggs may be due to 1) inadequacies of level of certain nutrients of eggs required for developing their ovarioles or eggs, 2) it could be caused also by the presence of an antifeeding factor in the eggs. The oviposition rate of Amblyseius swirskii on Achroia grisella eggs was higher than those fed on bee pollen (0.14 eggs/F), date pollen (8.7 eggs/F) and the acarid mite Tyrophagus putrescentiae (Schrank) (3.69 eggs/F) and comparable with those fed on Rhyncaphytoptus ficifoliae Keifer (20.0 eggs/F) (Diptilomiopidae) and the mango red spider mite Oligonychus mangiferus (Rahman and Sapra) (20.9 eggs/F) (Abou-Awad et al, 1999, 2010Riahi et al, 2017a,b). When Neoseiulus barkeri fed on Eutetranychus kankitus Ehara and Panonychus citri (McGregor) as natural prey, the oviposition rate was higher than those fed on Achroia grisella eggs presently (Ying Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The lower performance of Cydnoseius negevi towards Achroia grisella eggs may be due to 1) inadequacies of level of certain nutrients of eggs required for developing their ovarioles or eggs, 2) it could be caused also by the presence of an antifeeding factor in the eggs. The oviposition rate of Amblyseius swirskii on Achroia grisella eggs was higher than those fed on bee pollen (0.14 eggs/F), date pollen (8.7 eggs/F) and the acarid mite Tyrophagus putrescentiae (Schrank) (3.69 eggs/F) and comparable with those fed on Rhyncaphytoptus ficifoliae Keifer (20.0 eggs/F) (Diptilomiopidae) and the mango red spider mite Oligonychus mangiferus (Rahman and Sapra) (20.9 eggs/F) (Abou-Awad et al, 1999, 2010Riahi et al, 2017a,b). When Neoseiulus barkeri fed on Eutetranychus kankitus Ehara and Panonychus citri (McGregor) as natural prey, the oviposition rate was higher than those fed on Achroia grisella eggs presently (Ying Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Fiaboe et al, (2007) showed that life cycle of S. tridens Gordon durated 17.4 days when fed T. evansi Baker & Pritchard at 27 ° C. while, Taghizadeh et al , (2008a) stated that S .gilvifrons completed its life cycle after 12.49 days when fed on T urticae at 30 ° C. On the other hand, most phytoseiid species completed their life cycle at a constant temperature of 25-28 °C with in a range of 5-8 days (Fouly and EI-Laithy, 1992: Osman. 2000: Popov and Kondryakov, 2008Abou-Awad et a!., 2009 andA bad-Moyano et of., 2009). Whereas, Mahgoub (2006) stated that life cycle of N. cucumeris feamale durated 4.4, 6.6 and 6.3 days when reared on eggs, immatures and adults of T urticae respectively at 30 °C.…”
Section: Immatu••e Stagesmentioning
confidence: 99%